The Big Data Effect on Indonesia MSME with the Mediation of Differentiation Strategy and Innovation Performance - Young, Meishelle Andriani; Sudharthio, Lily (Bina Nusantara University, 2025)
In Indonesia, micro, small, and medium enterprises (MSMEs) drive economic growth, contributing 61.1% of GDP, with fashion as the second-largest sector. As e-commerce expands, MSMEs can harness big data through cloud platforms to boost innovation and competitiveness. The research investigates how big data adoption enhances MSMEs’ performance in Indonesia’s fashion industry, focusing on its role in decision-making, differentiation strategies, and operational outcomes. The research surveyed 228 MSME owners, combining quantitative data and interviews to assess big data’s impact on customer engagement, innovation, and efficiency. Findings reveal that leveraging big data significantly strengthens performance by refining decision-making and accelerating innovation. Key factors like data volume (scale), velocity (speed), and variety (diversity) directly influence success. Differentiation strategies—such as unique product designs or tailored marketing—mediate the link between data use and improved business outcomes. Challenges persist while the research underscores the urgency for MSMEs to adopt data-driven practices. Limited tech infrastructure and low digital literacy hinder progress among small-scale owners. To thrive, businesses must prioritize investments in cloud tools and skills training, while policymakers should support affordable tech access. This research offers practical insights for MSMEs aiming to navigate competitive e-commerce landscapes, emphasizing that innovation and adaptability, powered by data, are critical for sustainable growth.